Management Control System for Company X - Ardy Susilo (iBuss Management, 2017)
In this globalization era, the competition between businesses are getting unimaginable tighter. Customer nowadays demand more and more – they want better, faster, and cheaper products. For these reasons, many businesses suffers in regards to losing sales and brand awareness. As one of the leading market researcher, Company X is also facing the same problem. Their customers demand market research results that are both valid and reliable. This demand is hard to fulfil by Company X because there are many factors that affect the quality of market research results. The purpose of this dissertation is to come up with a set of management control system that can be implemented by Company X to improve the quality of their market research results. Qualitative research method will be used by the writer by conducting interview with Company X’s manager and employee to find out the current management control system that is present in the company. The findings of this research gives a better control for Company X to make sure high quality market research results. Keywords: Market Research, Supplier, Employee, Control, Quality